(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Diabetes mellitus is a chronic metabolic disorder which affects carbohydrate, lipid and protein metabolism. There is a strong relation between some specific oligoelements and diabetes mellitus. The study was undertaken to determine serum levels of zinc and magnesium in 60 newly diagnosed uncomplicated type 2 diabetic (group I) and 60 healthy non-diabetic subjects (group II). Serum zinc and magnesium were estimated by Atomic Absorption Spectrophotometer (AAS). The serum zinc and magnesium levels were (72.70±8.43 ?g/dl) and (1.85±0.17 mg/dl) respectively in group-1 and (75.92±8.20 ?g/dl) and (2.00±0.17 mg/dl) respectively in group-11. The levels were significantly decreased in group-1. Study showed that type 2 diabetes mellitus can result in changes in zinc and magnesium levels and supplementation of both zinc and magnesium may be considered in those cases. DOI: http://dx.doi.org/10.3329/bjmb.v3i2.13811 Bangladesh J Med Biochem 2010; 3(2): 46-49